Repercussions in educational reform from the perspective of the student (2015)
ABSTRACT: Educational policies are tools that the state prepares to generate conditions that allow access to and retention in schools, with the consequent reduction in school failure, increasing the external yield and fulfilling the expectations of the internal agents (teachers, students, school managers), external users (families, society, employers, industrialists) and the great expectations of the national project and the political pundits who see education as the panacea to all the evils and crises of nations.